The Conventional Option - Gregory Koger; Sergio J. Campos (Washington University Law Review, 2014)
The filibuster in the United States Senate effectively imposes a supermajority vote requirement to pass any legislation. Both supporters and critics of the filibuster agree that any filibuster reform would require extraordinary measures. In contrast to this consensus, this Article describes a method we call the “conventional option,” which allows the filibuster to be reformed by a simple majority of senators at any time using ordinary Senate procedures. As we show below, a majority of senators using the conventional option (1) cannot be filibustered; (2) can act on any day the Senate is in session (not just at the beginning of a new Congress); and (3) does not need to invoke the Constitution. In fact, this Article shows that both the U.S. House of Representatives and the Senate have limited filibustering in the past by using the conventional option described here.
Keywords: supermajority vote; filibuster; filibuster reform; conventional option; simple majority; Senate; Senate procedures